2011
DOI: 10.14499/indonesianjcanchemoprev2iss1pp141-145
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Activity of Ethanolic Leaves Extract and Its Different Solvent Fractions of Piper betle L. In Vitro

Abstract: Various diseases including cancer and cardiovascular diseases are induced by free radicals via lipid peroxidation, protein peroxidation, DNA damage, and cellular degeneration in the cells. Piper betle L., commonly called betel, belongs to the Piperaceae family. It originated from South and South East Asia, and has been used as a traditional medicine by people there due to its medicinal properties. In the present study, free radical scavenging activity of ethanolic leaves extract of Piper betle L. together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(13 reference statements)
0
2
0
1
Order By: Relevance
“…Pada penelitian kesepuluh menunjukkan aktivitas penangkap radikal DPPH ekstrak etanolik daun, fraksi heksana, fraksi etil asetat, fraksi butanol dan fraksi air dari Piper betle L., serta EGCG sebagai standar. bahwa memiliki aktivitas penangkap radikal bebas DPPH tertinggi dari semua fraksi pada 25 g/ml (Risdian, et al 2011).…”
Section: Hasil Dan Pembahasanunclassified
“…Pada penelitian kesepuluh menunjukkan aktivitas penangkap radikal DPPH ekstrak etanolik daun, fraksi heksana, fraksi etil asetat, fraksi butanol dan fraksi air dari Piper betle L., serta EGCG sebagai standar. bahwa memiliki aktivitas penangkap radikal bebas DPPH tertinggi dari semua fraksi pada 25 g/ml (Risdian, et al 2011).…”
Section: Hasil Dan Pembahasanunclassified
“…To attain stability, free radicals damage or react with neighboring molecules. External origin of free radicals are X-rays, ozone, cigarette smoke, industrial chemicals, ultraviolet light, and environmental pollutants 1,2 . Imparity between Reactive Oxygen Species (ROS) and the anti-oxidative defense systems cause oxidative stress that could lead to many diseases such as cancer, cardiovascular diseases, rheumatoid arthritis, and atherosclerosis 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Those piper extracts were also compared to eugenol which had an IC 50 value of 3.8 µg/mL. Risdian et al1 . suggested that DPPH scavenging activity of P. betle L. ethanol extract was strong with an IC 50 value of 3.48 µg/mL.…”
mentioning
confidence: 99%